Synthesis of superhydrophobic polymer/tungsten (VI) oxide nanocomposite thin films - Dixon, Sebastian; Noor, Nuruzzaman; Sathasivam, Sanjayan; Lu, Yao; Parkin, Ivan (European Journal of Chemistry, 2016)
A method is presented to enable the preparation of superhydrophobic polymer/tungsten (VI) oxide (WO3) nanocomposite coatings on glass substrates. WO3 nanoparticles were incorporated via the swell-encapsulation-shrink method into superhydrophobic silicone polymer films deposited on glass via aerosol-assisted chemical vapour deposition (AACVD) to produce the novel nanocomposite films. The technique overcomes the limitations of previous methods for nanoparticle incorporation to provide a synthetic route to previously unattainable materials. The nanocomposite films retain the properties of the superhydrophobic polymer while the presence of the nanoparticles is clearly evident. As such, the films have a range of potential applications including high surface area photocatalysis and self-cleaning photochromic or electrochromic coatings. The two-stage synthesis is shown to be flexible and suggests great scope for producing any number of future novel materials. The thin films were characterized using scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) analysis, X-ray photoelectron spectroscopy (XPS), infra-red (FTIR) spectroscopy, X-ray diffractometry (XRD) and water droplet contact angle measurements.